Composition Form and Function Configuration of Intelligent Terminal Based on Edge Computing for Power Internet of Things. Issue 1 (January 2021) - Liang, Xiaolin; Sun, Donglei; Li, Wensheng
Abstract: The intelligent terminal is a key device in the Power Internet of Things (PIOT), which plays a core role in the process of accurately sensing the state of power equipment and adjusting the user's electricity behaviour in real time. As a decentralized computing architecture, edge computing plays an important role in improving the data processing capacity and operation reliability of PIOT. This paper describes the operation process of PIOT based on edge computing, by studying the form of intelligent terminals in the field of power transmission, distribution and consumption, putting forward the basic configuration, specific function and principles of intelligent terminal. Combined with the operation characteristics and actual demand of power system, the application analysis of information perception ability and online control ability of intelligent terminal is carried out.